Association of surgical hematoma evacuation vs conservative treatment with functional outcome in patients with cerebellar intracerebral hemorrhage - Kuramatsu, Joji Benjamin; Ringleb, Peter A.; Purrucker, Jan; Rizos, Timolaos (The journal of the American Medical Association, 2019)
Importance The association of surgical hematoma evacuation with clinical outcomes in patients with cerebellar intracerebral hemorrhage (ICH) has not been established. Objective To determine the association of surgical hematoma evacuation with clinical outcomes in cerebellar ICH. Design, Setting, and Participants Individual participant data (IPD) meta-analysis of 4 observational ICH studies incorporating 6580 patients treated at 64 hospitals across the United States and Germany (2006-2015). Exposure Surgical hematoma evacuation vs conservative treatment. Main Outcomes and Measures The primary outcome was functional disability evaluated by the modified Rankin Scale ([mRS] score range: 0, no functional deficit to 6, death) at 3 months; favorable (mRS, 0-3) vs unfavorable (mRS, 4-6). Secondary outcomes included survival at 3 months and at 12 months. Analyses included propensity score matching and covariate adjustment, and predicted probabilities were used to identify treatment-related cutoff values for cerebellar ICH. Results Among 578 patients with cerebellar ICH, propensity score-matched groups included 152 patients with surgical hematoma evacuation vs 152 patients with conservative treatment (age, 68.9 vs 69.2 years; men, 55.9% vs 51.3%; prior anticoagulation, 60.5% vs 63.8%; and median ICH volume, 20.5 cm3vs 18.8 cm3). After adjustment, surgical hematoma evacuation vs conservative treatment was not significantly associated with likelihood of better functional disability at 3 months (30.9% vs 35.5%; adjusted odds ratio [AOR], 0.94 [95% CI, 0.81 to 1.09],P = .43; adjusted risk difference [ARD], −3.7% [95% CI, −8.7% to 1.2%]) but was significantly associated with greater probability of survival at 3 months (78.3% vs 61.2%; AOR, 1.25 [95% CI, 1.07 to 1.45],P = .005; ARD, 18.5% [95% CI, 13.8% to 23.2%]) and at 12 months (71.7% vs 57.2%; AOR, 1.21 [95% CI, 1.03 to 1.42],P = .02; ARD, 17.0% [95% CI, 11.5% to 22.6%]). A volume range of 12 to 15 cm3was identified; below this level, surgical hematoma evacuation was associated with lower likelihood of favorable functional outcome (volume ≤12 cm3, 30.6% vs 62.3% [P = .003]; ARD, −34.7% [−38.8% to −30.6%];Pvalue for interaction, .01), and above, it was associated with greater likelihood of survival (volume ≥15 cm3, 74.5% vs 45.1% [P < .001]; ARD, 28.2% [95% CI, 24.6% to 31.8%];Pvalue for interaction, .02). Conclusions and Relevance Among patients with cerebellar ICH, surgical hematoma evacuation, compared with conservative treatment, was not associated with improved functional outcome. Given the null primary outcome, investigation is necessary to establish whether there are differing associations based on hematoma volume.